Speaking anxiety in young EFL ecuadorian students - Ocaña Ramos, Diana Elizabeth (2021)
This paper aims to determine the causes of speaking anxiety among EFL teenagers from Unidad Educativa Municipal Quitumbe. Teenage learners are influenced by different types of feelings during adolescence due to the specific psycho-physiological changes of this age group. Therefore, teachers must be incredibly careful on how foreign language anxiety negatively influences the personality of learners from the point of view of their character and confidence building. According to the surveys administered during this investigation, most of the students find it difficult to learn, understand and use the foreign language. This phenomenon is the result of the interaction of several factors, which is why, it is paramount to identify the causes of foreign language anxiety, particularly in speaking for it is in the communicative act where anxiety is most visible. To obtain the data, it was considered necessary to make use of the previously used and tested Foreign Language Classroom Anxiety Scale (FLCAS), which was taken into consideration as guide. The findings present a high level of speaking anxiety in the foreign language class due to the poor knowledge of verbal and non-verbal skills (See in results pgs. 12-18). This paper suggests that further research about this phenomenon within Ecuadorian students is of the highest importance.